A Survey of Parental Involvement to the Students' English Learning Achievement at SMA Negeri 1 Muara Beliti - Yenni Yunaini (LP3MKIL, 2024)
The research aimed to find out what was parental involvement in students’ English learning achievement at SMA Negeri 1 Muara Beliti. The design of this research was a cross-sectional survey as part of quantitative research. The population of this research was eleventh grade students of SMA Negeri 1 Muara Beliti. The total number of population was 162 students. In taking the sample of the research, the researcher used purposive sampling by students high score on English learning the sample was 49 participants of parents. The data in this research was obtained from questionnaires about parental involvement. The data was analyzed by using percentage. The results of the research indicate that parental involvement was strong categorized at SMA Negeri 1 Muara Beliti. Keywords : Survey, Parental Involvement, English Learning Achievement